(untitled) (The Pakistan Development Review, 2007)
Two major problems promise to dominate economic and social policy during the twentyfirst century. These are global climate change and the growing gap between the rich and the poor. Economists are facing these issues at a time when many of the standard tools of economic analysis—for example, competitive general equilibrium and the theoretical system that supports it—have fallen into disfavour in analysing global issues involving uncertainty and irreversibility. This is both a challenge and an opportunity for development economics. This paper first examines economic models of human development and climate change, drawing, where possible, on the situation in Pakistan. We then outline an approach to coping with climate change based on new perspectives in behavioural and development economics, and on the likely consequences of global warming for Pakistan. We focus on adaptation to climate change rather than on mitigation strategies.